2018
DOI: 10.1177/0963689718755778
|View full text |Cite
|
Sign up to set email alerts
|

Microenvironment Imbalance of Spinal Cord Injury

Abstract: Spinal cord injury (SCI), for which there currently is no cure, is a heavy burden on patient physiology and psychology. The microenvironment of the injured spinal cord is complicated. According to our previous work and the advancements in SCI research, ‘microenvironment imbalance’ is the main cause of the poor regeneration and recovery of SCI. Microenvironment imbalance is defined as an increase in inhibitory factors and decrease in promoting factors for tissues, cells and molecules at different times and spac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
247
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 369 publications
(253 citation statements)
references
References 153 publications
(177 reference statements)
0
247
0
6
Order By: Relevance
“…In contrast, the Mus response is typical of wounding in most mammals, namely the generation of a pro‐inflammatory environment by the production of cytokines secreted by leukocytes, neutrophils, macrophages, microglia, and fibroblasts. These cytokines attract additional blood cells and macrophages to the wound site and can assist with the induction of neurotrophins (Fan et al, ), but excess levels cause scarring (Werner & Grose, ). This self‐reinforcing system can induce fibrosis and subsequent inhibition of axonal regrowth across a spinal lesion.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the Mus response is typical of wounding in most mammals, namely the generation of a pro‐inflammatory environment by the production of cytokines secreted by leukocytes, neutrophils, macrophages, microglia, and fibroblasts. These cytokines attract additional blood cells and macrophages to the wound site and can assist with the induction of neurotrophins (Fan et al, ), but excess levels cause scarring (Werner & Grose, ). This self‐reinforcing system can induce fibrosis and subsequent inhibition of axonal regrowth across a spinal lesion.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the Mus response is typical of wounding in most mammals, namely the generation of a pro-inflammatory environment by the production of cytokines secreted by leukocytes, neutrophils, macrophages, microglia, and fibroblasts. These cytokines attract additional blood cells and macrophages to the wound site and can assist with the induction of neurotrophins (Fan et al, 2018), but excess levels cause scarring (Werner & Grose, 2003). This self-reinforcing system can induce fibrosis and subsequent inhibition of axonal regrowth across a spinal lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Spinal cord transaction (SCT), a serious damage to nerves which run inside the vertebral column, results in irreversible loss of function at the level and below of injured location, and currently there is no cure [109]. A major reason for the poor prognosis of SCT is associated with neuronal loss and the extremely weak regenerative capacity of axons of the central nervous system after injury; although there is some inherent regenerative capacity of the central nervous system, it is very limited [110]. A recent study revealed the association of eIF5A1 with the neuroplasticity and functional recovery after SCT [111].…”
Section: Neural Diseasesmentioning
confidence: 99%